U-turn - Ridley, John, 1965- (Coronet Books, 1998)
A very funny black comedy about a gambler whose car breaks down near an Arizona mining town filled with thieves, vamps, and killers. Directed by Stone, starring Sean Penn, Nick Nolte, and Jennifer Lopez. 20 b/w photos.